Advances in the combination of CAR-T therapy with small-molecule reagents for hematologic malignancies - Yang, Baiyan; Su, Yang; Wang, Chunling; Yu, Liang (Frontiers in Immunology, 2025)
Chimeric antigen receptor T-cell (CAR-T) therapy has become a cornerstone of the treatment for hematologic malignancies. However, as a monotherapy, it still faces major challenges such as therapy resistance, disease relapse, and minimal residual disease (MRD) persistence post-remission. Small molecule compounds, such as Bruton’s tyrosine kinase (BTK) inhibitors, hypomethylating agents, and immunomodulatory drugs, can augment the antitumor efficacy of CAR-T cells through multiple mechanisms, enhancing their persistence and the proliferative capacity. Combination therapy enables a synergistic attack on malignant cells to effectively eliminate MRD, overcome resistance, and improve overall therapeutic outcomes. To date, the combining of CAR-T therapy with small molecule agents has shown promising clinical potential in the treatment of hematologic malignancies, including acute lymphoblastic leukemia (ALL), diffuse large B-cell lymphoma (DLBCL), chronic lymphocytic leukemia (CLL) and multiple myeloma (MM). This review provides a comprehensive overview of the efficacy, safety and synergistic mechanisms of CAR-T therapy combined with Small-molecule reagents, and proposes optimization strategies to enhance clinical efficacy and minimize the adverse effects which may pave the way for future therapeutic development.